Educations for women - Moore, Mrs. Elda Lenore (My University, 1896)
Introduction: One of the great facts of our time, is the advancement which is being made in the education of women, It is a bold, forward movement, full of importance, and one that should attract the attention of every American citizen. Society is actively awakened to it, and although critics may find fault with it, yet for all this there are good intentions and an earnest spirit behind it.
Citation: Moore, Mrs. Elda Lenore. Educations for women. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Advancement; Education; Women; Society; Theses; Manuscripts (documents)